FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN PULAU MOROTAI - Nurhikmah Sibua; Lukman Wangko; Arkal Lotar (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to determine the factors that influence the regional original income of Morotai Island Regency. The type of research used is descriptive qualitative analysis. Collecting qualitative descriptive analysis data by means of observation, interviews, and documentation. The results of this study are the performance of regional financial management describing the performance of the Morotai Island Regency government at the level of decentralization, the degree of contribution of regional original revenue to total regional revenue, regional financial capacity is still very low, and the factors that influence Regional Original Revenue in Regional Financial and Asset Management Revenue Agency Morotai Island Regency; The factor of the minimal contribution of restaurants and hotels in optimizing the sources of regional original revenue, the factor of the ineffectiveness of related agencies or agencies in optimizing the sources of regional original revenue; and the population factor for the regional original income of Morotai Island Regency.